Significant upregulation of small heat shock protein αA-crystallin in retinal detachment. (December 2019) - ,; Cebulla, Colleen M.; Van Law, Heather; Heisler-Taylor, Tyler; Hamadmad, Sumaya; Shah, Mohd Hussain; Kim, Bongsu; Davidorf, Frederick H.; Ohr, Matthew; Wells, Michael; Yanoga, Fatoumata; Chang, Susie; et al.
Highlights: αA-crystallin is a small heat shock protein involved in neuroprotection during stress. αA-crystallin is significantly upregulated in murine experimental RD at the transcriptional and translational levels. αA-crystallin levels are significantly increased in the vitreous samples from pseudophakic patients with RD. Our data provide a platform for further studies to evaluate the potential therapeutic value of αA-crystallin in RD.